Successful repair of a penetrating wound of the thoracic aorta. - Ramanathan, T (1975)
Penetrating wounds of the aorta are not necessarily fatal. A successfully managed patient with a stab wound of the ascending aorta is reported, and some problems of management associated with such injuries are discussed.